Prevalence of HIV-1/2, HTLV-I/II, hepatitis B virus (HBV), hepatitis C virus (HCV), Treponema pallidum and Trypanosoma cruzi among prison inmates at Manhuaçu, Minas Gerais State, Brazil - Bernadette Corrêa Catalan-Soares; Regina Toledo P. Almeida; Anna Bárbara F. Carneiro-Proietti (Revista da Sociedade Brasileira de Medicina Tropical, 2000)
The purpose of this study was to determine the seroprevalence of human immunodeficiency virus (HIV-1/2), human T-cell lymphotropic virus (HTLV-I/II), hepatitis B virus (HBV), hepatitis C virus (HCV), Treponema pallidum and Trypanosoma cruzi among 63 male prisoners in Manhuaçu, Minas Gerais, Brazil and to compare this with data from eligible blood donors. The positive results were as follows: 11/63 (17.5%) for HBV, 5/63 (7.4%) for syphilis, 4/63 (6.3%) for HCV, 3/63 (4.8%) for Chagas' disease, 2/63 (3.2%) for HIV-1/2 and 1/63 (1.6%) for HTLV-I/II. The seroprevalence in prisoners was higher than among blood donors, mainly for antibodies to HIV-1/2, HCV and HBV. This is probably due to low social economic level, illiteracy, higher proportion with a prior history of intravenous drug use and/or unsafe sexual behavior. Therefore, these prisoners constitute a high risk group and routine screening and counseling are recommended.